Risk factors for a persistent gastrocutaneous fistula following gastrostomy device removal: A tertiary center experience - Abdulrahman Alshafei; Dawn Deacy; Brice Antao (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of this study is to identify the risk factors for a persistent gastrocutaneous fistula (GCF) after gastrostomy device (GD) removal in children. Materials and Methods: A retrospective analysis of 59 patients that underwent GD insertion and removal over an 11-year period (2005-2015). Patients were divided into two Groups (A and B) according to persistence or closure of the gastrocutaneous tract. Data included patient demographics, comorbidities, age at insertion, gastrostomy site infections, size and type of device, duration of placement, and method of insertion and removal. Statistical analysis was done using Chi-square test and ANOVA test where P < 0.05 was considered statistically significant. Results: A total of 34 patients (Group A) developed a GCF post-GD removal. The gastrostomy tract closed spontaneously in 25 patients (Group B). Underlying comorbidities did not influence spontaneous closure. Younger age at insertion (<2 years), longer duration of device placement, open gastrostomy insertion, upsizing the GD, changing a gastrostomy tube to a button, and site infections were significant risk factors for a persistent GCF. Conclusions: Risk analysis of persistent GCF is important for patient counseling before removal or replacement of the GD. We have identified a number of potentially reversible risk factors for a persistent GCF and have made recommendations accordingly.